Introduction to Biochemical Genetics from the Clinical Laboratory Prospective: A Case-Based Discussion - Irene De Biase; Margarita Diaz-Ochu; Mary Rindler; Wendy L. Hobson-Rohrer (Association of American Medical Colleges, 2017)
Introduction Inborn errors of metabolism (IEM) are individually rare, but their cumulative frequency is high. Most importantly, IEM are in the differential diagnosis for common clinical emergencies and childhood illnesses. Biochemical genetics (BCG) testing is used to diagnose IEM or follow-up with patients after treatment. A basic grasp of the strengths and limitations of biochemical testing is critical for clinicians to understand test results, identify when to seek a consultation with a specialist, or explain results to patients. Methods This resource is designed as an introduction to BCG testing for aminoacidopathies and urea cycle disorders, and includes eight cases. The resource was first developed for the Genetic Counseling Graduate Program at the University of Utah School of Medicine, and used in the last 2 years in small-group settings, where students were each engaged with one case (eight per session). Results Overall, students gave high ratings to the effectiveness of the examples used, and the interactive format encouraged students' questions. The resource has been tested with medical students and residents rotating through the Maternal Newborn Care Unit at the University Hospital. In this setting, a small-group case-based discussion was used. As expected, prior knowledge of IEM or BCG testing was low. Confidence in evaluating BCG testing after completing the learning activity improved. Discussion This resource facilitates the integration of specialized knowledge of IEM in a primary care-oriented setting. Genetics counseling students' feedback demonstrated the overall success of this activity in the specialized, genetics-oriented setting.